Quantum confined Stark effect of InGaN/GaN multi-quantum disks grown on top of GaN nanorods. - Park, Y; Holmes, M; Kang, T; Taylor, R (2010)
We have investigated, using micro-photoluminescence, the quantum confined Stark effect in an In(x)Ga(1-x)N/GaN multi-quantum disk structure at the tip of a single GaN nanorod. A strong and sharp emission line from the In(x)Ga(1-x)N/GaN quantum disks near 3.26 eV was observed. The peak energy of the emission line was observed to blue-shift with increasing excitation power, indicating a quantum confined Stark effect. Furthermore, both the blue-shift and the intensity of the emission saturate with increasing excitation power. The temperature-dependence of the 3.26 eV emission line has also been investigated.